Distribution of Region 1 and 2 currents in the quiet and substorm time plasma sheet from THEMIS observations - Jiang Liu; V. Angelopoulos; Xiangning Chu; R. L. McPherron (Geophysical Research Letters)
Abstract Although Earth's Region 1 and 2 currents are related to activities such as substorm initiation, their magnetospheric origin remains unclear. Utilizing the triangular configuration of THEMIS probes at 8–12 RE downtail, we seek the origin of nightside Region 1 and 2 currents. Our statistical study reveals that both kinds of currents exist in the plasma sheet during quiet and active times. Region 2 currents are deep inside the plasma sheet; Region 1 currents, which are farther away from the neutral sheet, extend to the plasma sheet boundary layer. At geomagnetic quiet times, the separation between the two currents is located ~2.5 RE from the neutral sheet. During substorms, the separation migrates toward (away from) the neutral sheet as the plasma sheet thins (thickens). These findings suggest that the plasma sheet is a source of Region 1 and 2 currents and its deformation is associated with redistribution of FAC sources in the magnetotail.